Ecological Study of Mosquito Larvae Breeding Site Anopheles Malaria Vector in Abandoned Ponds Hanura Village - Setyaningrum, Endah; Qoyima, Allafia; Priyambodo, Priyambodo; Pratami, Gina Dania (Berkala Ilmiah Biologi, 2025)
Malaria is an infectious disease that is common in tropical and sub-tropical climates, making malaria endemic areas. One of the villages in Teluk Pandan District, Pesawaran Regency, Hanura Village is close to an abandoned pond which is a breeding place for malaria vectors which is the cause of malaria cases in Pesawaran. The aim of this research is to determine the relationship between physical and chemical factors and the density of Anopheles larvae and to identify types of aquatic plants and aquatic animals and their influence on the density of Anopheles mosquito larvae. in Hanura Village, Teluk Pandan District. The method used in this research is a survey method and observation of several ecological factors in the breeding places of malaria mosquito vectors. The measurement results showed that physical and chemical factors in DO had a positive correlation with larval density. Biological factors found include chicken stomach moss (Enteromorpha intestinalis), sea turtles (Limnoporus canaliculatus), back swimmers (Notonecta undulata), snakehead fish (Channa striata), water beetles (Tropisternus sp.), and tadpoles (Anura). The higher the population of aquatic plants, the higher the density of mosquito larvae. Meanwhile, the higher the population of aquatic animals, the lower the density of mosquito larvae.